Digital accessible knowledge: Mobilizing legacy data and the future of taxonomic publishing - Fawcett, Susan; Agosti, Donat; Cole, Selina R.; Wright, David F. (Bulletin of the Society of Systematic Biologists, 2022)
No abstract available.